Computational intelligence, educational robotics, and artificial intelligence in the educational field. A bibliometric study and thematic modelling - Colina Vargas, Alejandra Mercedes; Espinoza Mina, Marcos Antonio; López Catálan, Luis; López Catalán, Blanca (IJERI: International Journal of Educational Research and Innovation, 2024)
This study addresses the convergence between technology and education, exploring the impact of paradigms such as "computational intelligence," "educational robotics," and "artificial intelligence" in educational research. The methodology was defined in three stages. In the first stage, the Web of Science database was chosen, and a search string was developed. The second stage involved the selection of studies through inclusion/exclusion criteria and the use of PRISMA. The third stage included the extraction and analysis of quantitative and qualitative data, using bibliometric software, content analysis, and tools such as R Studio, Bibliometrix, VOSViewer, and Python. An annual growth of 56.51% between 2019 and 2023, with 208 works, is revealed. "Sustainability" leads the journals with 39 articles, indicating concentration in highly productive journals. The analysis of keyword co-occurrence reveals frequents thematic areas, highlighting "artificial intelligence," "education," "technology," "machine learning," and "Big data." The lead institution is the Chinese University of Hong Kong, while China stands out with 61 papers at the country level. It emphasizes the importance of considering quality and quantity in scientific production and identifies five key topics in research summaries, suggesting areas of research focused on the integration of technology and educational innovation.